(untitled) (MAUSAM, 1957)
To supplement available observed winds at high levels, about 40 special ascents were made with big balloons at Poona in winter ’1952-53. Tails of 200 metros were attached and weighted to reduce slant. 15 of the ascents reached heights above 60,000 feet. The paper gives–(i) height time curves of the individual ascents, iii) vertical time section diagrams for the four months upto 22 km, with isotachs and general wind directions and (iii) diagrams of departures from normal of temperatures upto 16 km from daily radiosonde ascents, The vertical currents and winds are discussed in relation to the synoptic situations and major temperature changes.